2017
DOI: 10.1007/s00192-017-3278-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraurethral bulking agents for the management of female stress urinary incontinence: a systematic review

Abstract: There are a range of complications associated with UBAs, the most common being urinary tract infection. However, it remains a very well tolerated procedure in the majority of patients. UBAs should be considered as an alternative in patients unsuitable for more invasive procedures and those willing to accept the need for repeat injections. The majority of the literature focuses on subjective improvement measures rather than objective improvement measures. Further randomized controlled trials directly comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 28 publications
0
46
0
4
Order By: Relevance
“…Meta‐analyses have been reported for single agents, such as Macroplastique . Recently, a systematic review which focused principally on the safety and efficacy of Macroplastique and Bulkamid has been published . However, there exists no meta‐analyses or systematic reviews evaluating all of the recently available bulking agents in the treatment of SUI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta‐analyses have been reported for single agents, such as Macroplastique . Recently, a systematic review which focused principally on the safety and efficacy of Macroplastique and Bulkamid has been published . However, there exists no meta‐analyses or systematic reviews evaluating all of the recently available bulking agents in the treatment of SUI.…”
Section: Methodsmentioning
confidence: 99%
“…In their recent systematic review focusing mainly on Bulkamid™ and Macroplastique™, Siddiqui et al have found out that urinary tract infection (UTI) was the most common adverse effect of UBT, with an overall incidence approximating 11%. Implantation site pain and acute urinary and dysuria were the other leading complications which were encountered in 5‐10% of the patients . de Vries et al, who conducted a more extensive literature review on complications associated with the bulking agents used in the clinical practice in the last 15 years, identified a total of 2095 complications in 6462 patients and 110 complications in 49 patients who were involved in 79 original studies and 38 case reports, respectively .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohort studies of bulking agent Urolastic report results lower to this threshold with subjective and objective cure rates of 56% to 68% and 59% to 65%, respectively, after 6‐ and 12‐month follow‐up . A systematic review of other bulking agents show on the other hand subjective and objective success rates up to 89% and 73% …”
Section: Discussionmentioning
confidence: 99%
“…With a low complication rate of 0% to 5.7%, the safety profile seems to be better than MUS surgery . Variable clinical success rates of UBA of 50% to 89% after 1‐year follow‐up are reported . The National Institute for Health and Care Excellence and the European Association of Urology (EAU) guidelines recommend UBA to be used for short‐term management of SUI if conservative management has failed.…”
Section: Introductionmentioning
confidence: 99%